SIX SIGMA UNTUK PERBAIKAN LAYANAN RESEP DI RS X KOTA SEMARANG - Sri Suwarni; Metrikana Novembrina (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
Six sigma is an improvement method that focuses on output quality improvement free from defects and important value for customers. Based on pharmacy service standards at the Hospital, that at each stage of the prescription service flow, efforts were made to prevent the occurrence of medication errors. The purpose of this study was to determine the performance of prescription services in outpatient pharmacy installations by calculating potential medication error events analyzed with Six Sigma used to determine the priority of quality improvement output, namely a decrease in defects in prescription services. observational descriptive research design, the population of this study were outpatient pharmacy patients, sampling techniques with probability sampling method. The sample in this study were 150 recipes. Using the instrument, check the observation sheet for counting medication errors. There are 5 stages of problem solving in the Six Sigma method, they are define, measure, analyze, analyze, and control. The value of the service performance prescription value, yield = 92.98%, defect = 6.54%, meaning that the service performance of prescription of RSI Sultan Agung outpatient pharmacy unit which still gives the opportunity for the emergence of medication error is 6.54%. If the sigma 2.146 is still needed an improvement in the performance of prescription services. Calculated sigma levels are priority improvements in the phase of clinical prescribing, pharmacy prescribing, administrative prescribing, transcribing, and dispensing to improve patient safety